STUDY THE ACCURACY OF MICRONETWORK FOR PRECIS ENGINEERING PROJECTS - N. Sayle, Khamis (Iraqi Journal of Civil Engineering, 2007)
Abstract The rapid development in computer technology helped to overcome the problem of accuracy improvement and accuracy assessment of high precision network. In this paper a study was conducted to evaluate and compare the accuracy of position through the area of error ellipses in case of using single base line and two base lines for geodetic monitoring network of Haditha Dam . The present paper purpose is to conclude that the use of additional baseline is an important part in the improvement of micronetwork accuracy and treats the weakness in the geometrical figures used.